2009
DOI: 10.1038/ncb1901
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and spreading of tauopathy in transgenic mouse brain

Abstract: Hyperphosphorylated tau makes up the filamentous intracellular inclusions of several neurodegenerative diseases, including Alzheimer's disease 1. In the disease process neuronal tau inclusions first appear in transentorhinal cortex, from where they appear to spread to hippocampal formation and neocortex 2. Cognitive impairment becomes manifest when inclusions reach the hippocampus, with abundant neocortical tau inclusions and extracellular β-amyloid deposits being the defining pathological hallmarks of Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

68
1,474
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,568 publications
(1,550 citation statements)
references
References 35 publications
68
1,474
2
6
Order By: Relevance
“…the intercellular transfer of misfolded proteins has recently been demonstrated in several neurodegenerative diseases, including aLS [1][2][3], and it has been suggested that this mechanism is responsible for the progressive spread of pathology. Mutations in SOD1 (Cu/Zn-superoxide dismutase) cause 20 % of familial aLS, and these cases display similar clinical features and pathogenesis to sporadic aLS, which accounts for 90 % of all aLS cases.…”
Section: Introductionmentioning
confidence: 99%
“…the intercellular transfer of misfolded proteins has recently been demonstrated in several neurodegenerative diseases, including aLS [1][2][3], and it has been suggested that this mechanism is responsible for the progressive spread of pathology. Mutations in SOD1 (Cu/Zn-superoxide dismutase) cause 20 % of familial aLS, and these cases display similar clinical features and pathogenesis to sporadic aLS, which accounts for 90 % of all aLS cases.…”
Section: Introductionmentioning
confidence: 99%
“…Two-way ANOVA revealed no significant main effect for day (F (2, 162) = 2.221, P = 0.1118) and genotype (F (2, 162) = 1.862, P = 0.1587) during the A2 task (Figure 4f). On the P2 probe trial, the analysis of the percentage of time spent in the four quadrants revealed a significant main effect for quadrant (F (3,162) = 78.21, P o0.0001), no significant main effect for genotype (F (2,54) = 0.3026, P = 0.7402) but a significant quadrant × genotype interaction (F (6, 162) = 2.935, P = 0.0096) (Figure 4g). Post hoc Tukey's multiple comparisons test showed that the Tau DN/WT mice spend significantly less time in the target quadrant as compared with littermates ( Figure 4g).…”
Section: Generation Of Tau Dn Micementioning
confidence: 99%
“…Recent data suggest that a fraction of Tau protein is localized extracellularly. [1][2][3][4] However, the biological function of extracellular tau is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Injection of brain lysate containing aggregated forms of tau into mice that express WT human tau induced the formation of neurofibrillary tangles in the recipient mice. These spread beyond the injected hippocampus to more distant sites, including somatosensory cortex [43]. Immuno-depletion of tau from the injected material prevented induction of neurofibrillary tangles, confirming tau, and not a nonspecific "toxic factor" as the cause of pathology.…”
Section: Transcellular Spread Of Tau Pathology In Vitro and In Vivomentioning
confidence: 76%
“…Immuno-depletion of tau from the injected material prevented induction of neurofibrillary tangles, confirming tau, and not a nonspecific "toxic factor" as the cause of pathology. Finally, injection of P301S-containing brain lysate into mice that only express murine tau produced very limited pathology that was confined to the injection site [43]. This was reminiscent of the seeding barriers observed for PrP.…”
Section: Transcellular Spread Of Tau Pathology In Vitro and In Vivomentioning
confidence: 90%